THOP1 Is Entailed in a Genetic Fingerprint Associated with Late-Onset Alzheimer’s Disease - Sharlee Climer (Biomolecules)
In a systematic explorative study of genetic patterns on chromosome 19, we discovered a pattern comprising 23 SNP alleles that is significantly associated with late-onset Alzheimer’s disease (AD). This association was validated using two independent datasets. The pattern includes thimet oligopeptidase (THOP1), which has a long and disputatious relationship with AD. It also spans solute carrier family 39 member 3 (SLC39A3) and small glutamine-rich tetratricopeptide repeat co-chaperone alpha (SGTA) and is upstream from DIRAS family GTPase 1 (DIRAS1). We utilized population data to observe the frequencies of this genetic pattern for 11 different ancestries and noted that it is highly common for Europeans and relatively infrequent for Africans. This research provides a distinct genetic signature for AD risk, as well as insights into the complicated relationship between this disease and THOP1.